RANCANG BANGUN PENGENDALI IKLIM MIKRO PADA RUMAH TANAMAN BERBASIS MIKROKONTROLER - Diah Ajeng Setiawati; Joko Sumarsono; Asih Priyati; Guyup Mahardhian Dwi Putra; Muhammad Nasarudin (Universitas Muhammadiyah Mataram, 2021)
Control of temperature and humidity of air in plant houses which is microclimate control is necessary to do for optimal plant growth. The purpose of this research is to design and test the performance of microclimate control and monitoring systems in plant houses. Research tools and materials include plant houses, Arduino microcontrollers, DHT22 sensors, RTC DS3231, TFT LCD 128×64 12864, DC Pumps, 0.2 mm nozzles, relays, SD card modules, and exhaust fans. The method used is an experimental method of using a water misting system to control the temperature and humidity of the air. From the results obtained, the microclimate control design can work automatically assisted by DHT22 sensors. When the air temperature reaches > 29°C, the active air wasting fan releases hot air. Whereas when air humidity drops to <80%, active air humidifiers increase air humidity.